Does Self-Efficacy Moderate the Contribution of Metacognitive Awareness to Listening Comprehension? - Moh. Ana Usuludin; Rohmani Nur Indah (Institut Agama Islam Negeri (IAIN) Manado, 2021)
Does Self-Efficacy Moderate the Contribution of Metacognitive Awareness to Listening Comprehension? Current studies relate the issue of listening skills to several aspects. However, it still requires more empirical finding on the contribution of self-efficacy and metacognition toward listening comprehension. This study aimed to find the effect of metacognition on listening ability through self-efficacy and seek a suitable structural model. The chosen design was ex post facto research with a correlation using a path analysis model. This research was conducted at one of the state Islamic high schools in the city of Kediri. A total of 250 ten grader students participated in this research. Three instruments were used to collect data, including a closed questionnaire about self-efficacy, a closed questionnaire about students' metacognition sensitivity, and listening questions that adopted the TOEFL Junior Test. The results showed that the metacognitive influence model on listening did not significantly affect (p = .180), while the other two models showed a significant effect (metacognitive on self-efficacy, p = .000; self-efficacy on listening ability, p = .011). However, the indirect effect of students' metacognition abilities on listening ability through self-efficacy was significant at .059. Related to the path analysis model, the partial-mediated path analysis model was compiled, modified into a full-mediated model to meet the criteria of goodness of fit index.